Analisis Kemampuan Dasar Berbahasa Siswa Kelas IV di SDN 09 Serakim 1: Analysis of Basic Language Skills of Fourth Grade Students at SDN 09 Serakim 1 - Helaria Flafiana Ena; Fransisco Adam (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The importance of basic language skills in supporting elementary school students' communication, particularly in vocal delivery, speech, and intonation. Good language skills are not only determined by the clarity of the sounds produced, but also by the accuracy of pronunciation and the use of appropriate intonation so that the message can be understood well. However, observations and research data indicate that students' language skills still differ across aspects. The vocal aspect tends to be better than the other aspects, while the speech aspect remains a major weakness, and the intonation aspect falls into the sufficient category. This condition indicates that students' language skills have not developed evenly, so further study is needed to obtain a clearer picture of these abilities. This study aims to describe the basic language skills of fourth-grade students at SDN 09 Serakim 1, including vocal, speech, and intonation aspects. This study used a descriptive, qualitative approach with 4 students. Data collection was conducted through Likert-scale assessments of each observed aspect. The results showed that students' language skills vary across aspects. The vocal aspect obtained the highest percentage, 68.75%, in the good category; the intonation aspect, 56.25%, in the sufficient category; and the speech aspect, 43.75%, in the poor category. This indicates that students' abilities are quite good in vocal and intonation, but remain weak in speech. Thus, it can be concluded that students' basic language skills are unevenly distributed across all aspects, so more focused learning efforts are needed, especially to improve speech skills.